Cortex-wide neural interfacing via transparent polymer skulls - Leila Ghanbari (Nature Portfolio, 2019)
Imaging the mouse brain using glass cranial windows has limitations in terms of flexibility and long-term imaging. Here the authors engineer transparent polymer skulls that can fit various skull morphologies and can be implanted for over 300 days, enabling simultaneous high resolution brain imaging and electrophysiology across large cortical areas.